Investigating the influence of non financial incentives on employee motivation: a case of Coloursell Furnishers Pvt (Ltd). - Jayaguru, Jerry (Midlands State University, 2017)
The researcher’s main objective in carrying out the study was to investigate the influence of non financial incentives on employee motivation. The research was triggered by the researcher’s wish to improve the welfare of the workers at CF Pvt Ltd. This was in response to an outcry by the employees over poor remuneration, long working hours and poor working conditions at the organisation. These conditions caused an increase in the labour turnover rate. Turnover resulted in a loss of skilled labour which caused a decline in the quality of furniture manufactured which in turn caused an increase in the number of customer complaints and the chain of effects might be endless. The main objectives in conducting the study was to find the causes of labour turnover, find employee perceptions about the non financial incentives used by CF and to find the influence of non financial incentives on employee motivation. The researcher used the case study approach and a descriptive research design in collecting and analysing data. The sample size comprised of 40 respondents which included 25 employees, 10 former employees and 5 managers. Personal interviews were conducted on the management team and self administered questionnaires were issued on the employees and the former employees. Stratified, judgmental and snowballing sampling techniques were used in sampling the respondents. Results of the study showed that 65% of the employees were not satisfied with their jobs, the major causes of labour turnover were poor remuneration, long working hours and inappropriate fringe benefits. The results also showed that a majority of the employees were aware of the motivational techniques used by the management such as the use of fringe benefits but failed to appreciate these incentives. Research findings were presented using tables, graphs and pie charts. The researcher arrived to a conclusion that there is a positive relationship between the use of non financial incentives and employee motivation. However inadequacy or inappropriate mix of non financial incentives and financial incentives results in reduced motivation for the employees. The researcher made the following recommendations to the management and staff of CF. Training programmes should be tailor made to suit the demands of the customers so as to reduce customer complaints. Head office should give certificates to employees after their training courses so as to boost employee morale because this improves their CVs. Management should consult employees on what they prefer as fringe benefits so as to avoid giving employees benefits that they do not prefer.